Three-Dimensional Structure Characterization and Inhibition Study of Exfoliative Toxin D From Staphylococcus aureus - Ullah, Anwar; Khan, Ajmal; Al-Harrasi, Ahmed; Ullah, Kifayat; Shabbir, Asghar (Frontiers in Pharmacology, 2022)
The Staphylococcus aureus exfoliative toxins (ETs) are the main toxins that produce staphylococcal scalded skin syndrome (SSSS), an abscess skin disorder. The victims of the disease are usually newborns and kids, as well as grown-up people. Five ETs namely, exfoliative toxins A, B, C, D, and E have been identified in S. aureus. The three-dimensional (3D) structure of exfoliative toxins A, B, C and E is known, while that of exfoliative toxin D (ETD) is still unknown. In this work, we have predicted the 3D structure of ETD using protein modeling techniques (software used for 3D structure modeling comprising the MODELLER 9v19 program, SWISS-Model, and I-TESSER). The validation of the build model was done using PROCHECK (Ramachandran plot), ERRAT2, and Verify 3D programs. The results from 3D modeling show that the build model was of good quality as indicated by a GMQE score of 0.88 and by 91.1% amino acid residues in the most favored region of the Ramachandran plot, the ERRAT2 quality factor of 90.1%, and a verify3D score of >0.2 for 99.59% of amino acid residues. The 3D structure analysis indicates that the overall structure of ETD is similar to the chymotrypsin-like serine protease fold. The structure is composed of 13 β-strands and seven α-helices that fold into two well-defined six-strand β-barrels whose axes are roughly perpendicular to each other. The active site residues include histidine-97, aspartic acid-147, and serine-221. This represents the first structure report of ETD. Structural comparison with the other ETs shows some differences, particularly in the loop region, which also change the overall surface charge of these toxins. This may convey variable substrate specificity to these toxins. The inhibition of these toxins by natural (2S albumin and flocculating proteins from Moringa oleifera seeds) and synthetic inhibitors (suramin) was also carried out in this study. The results from docking indicate that the inhibitors bind near the C-terminal domain which may restrict the movement of this domain and may halt the access of the substrate to the active site of this enzyme. Molecular dynamic simulation was performed to see the effect of inhibitor binding to the enzyme. This work will further elucidate the structure–function relationship of this enzyme. The inhibition of this enzyme will lead to a new treatment for SSSS.